The Analysis of Pronouncing Post-Alveolar Fricative Faced by the English Education Students of Tanjungpura University - Pratama, Andra Sunata; Sada, Clarry; Ikhsanudin, Ikhsanudin (Universitas Muhammadiyah Sidoarjo, 2024)
The objective of this research is to describe the percentage of post-alveolar fricative sound pronunciation acceptability among the English Language Education students in their sixth semester at the University of Tanjungpura. The scope of the study would be limited to the comparison of the first and second formants of the participants with those of the native speaker, whose formants were evaluated utilizing the PRAAT software. The data was gathered from a pronunciation performance test that was conducted via an audio recording procedure. The study involved a total of 15 participants who were categorized into three distinct ethnic groups, including Indonesian Tionghoa, Dayak, and Malay. Each participant pronouncing a set of 20 words, consisting of both voiceless and voiced post-alveolar fricatives. According to the findings of the study, 1) the percentage of voiceless post-alveolar fricative sounds that were considered ‘Acceptable’ was 40.5%, whereas the percentage of those that were considered ‘Not Acceptable’ was 59.5%., 2) the percentage of ‘Acceptable’ pronunciation of voiced post-alveolar fricative sounds was 42%, while the percentage of those that were ‘Not Acceptable’ was 58%. The inference that can be drawn is that students encounter challenges when attempting to articulate post-alveolar fricative sounds. HIGHLIGHTS : The study revealed that 31% of students exhibited exceptional proficiency in voiceless post-alveolar fricative pronunciation, whereas 33% achieved excellence in voiced pronunciation. This indicates a diverse distribution of skill levels among students. The acceptable criteria for pronunciation show that pronunciations that fall within the excellent to fair categories are in agreement with the expectations of native speakers. The correct pronunciation was achieved in around 40.5% of cases for voiceless fricatives and 42% for voiced fricatives, indicating places where pronunciation was considered acceptable. A significant number of sixth-semester English Language Education students had obstacles in pronouncing post-alveolar fricatives. The study proposes the implementation of an appropriate educational setting, the development of phonetic learning awareness, and the investigation of curricular enhancements for addressing pronunciation difficulties.